Role of Serosal TRPV4-Constituted SOCE Mechanism in Secretagogues-Stimulated Intestinal Epithelial Anion Secretion - Cui, Yinghui; Chu, Fenglan; Yin, Kai; Chen, Xiongying; Wan, Hanxing; Luo, Gang; Dong, Hui; Xu, Feng (Frontiers in Pharmacology, 2021)
As little is currently known about the role of Ca2+ signaling in small intestinal epithelial anion secretion, we aimed to study its regulatory role in secretagogue-stimulated small intestinal anion secretion and the underlying molecular mechanisms. The intestinal anion secretion from native mouse duodenal epithelia was examined with Ussing chambers to monitor PGE2-, 5-HT-, and CCh-induced short-circuit currents (Isc). PGE2 (10 μM) and 5-HT (10 μM) induced mouse duodenal Isc, which was markedly attenuated by serosal Ca2+-free solution and selective blockers of the store-operated Ca2+ channels on serosal side of the duodenum. PGE2- and 5-HT-induced duodenal Isc was also inhibited by the ER Ca2+ chelator TPEN. However, dantrolene, a selective blocker of ryanodine receptors, inhibited PGE2-induced duodenal Isc, while LiCl, an inhibitor of IP3 production, inhibited 5-HT-induced Isc. Moreover, the duodenal Isc response to the serosal applications of both PGE2 and 5-HT was significantly attenuated in TRPV4 knockout mice. Finally, mucosal application of carbachol (100 μM) also induced duodenal Isc via selective activation of muscarinic receptors, which was significantly inhibited in serosal Ca2+-free solution but neither in mucosal Ca2+-free solution nor by nifedipine. Therefore, the serosal TRPV4-constituted SOCE mechanism is likely universal for the most common and important secretagogues-induced and Ca2+-dependent intestinal anion secretion. These findings will enhance our knowledge about GI epithelial physiology and the associated GI disease, such as diarrhea and constipation.